The influence of low molecular weight heparin medication on plasma DNA in pregnant women3. (4th September 2015) - Grömminger, Sebastian; Erkan, Sanli; Schöck, Ulrike; Stangier, Kerstin; Bonnet, Joachim; Schloo, Rüdiger; Schubert, Angela; Prott, Eva‐Christina; Knoll, Ute; Stumm, Markus; von Kalle, Christof; Hofmann, Wera
Abstract : What's already known about this topic? Until today the fetal fraction in cell‐free maternal plasma DNA is the most critical determinant for a successful NIPT analysis. What does this study add? We show for the first time since the introduction of NIPT into routine prenatal care that medication can influence NIPT results. To avoid discordant NIPT results our report provides guidance that blood sampling for NIPT should ideally occur right before the next application of low molecular weight heparin.